A6.29 In vitro protective effects of soluble klotho (SKL) protein on endothelial cells in systemic sclerosis (SSc). (13th February 2015) - Mazzotta, C; Romano, E; Bellando-Randone, S; Blagojevic, J; Guiducci, S; Matucci-Cerinic, M
Abstract : Background and objectives: Systemic Sclerosis (SSc) is an autoimmune connective tissue disease characterised by impairs angiogenesis, alterations of microcirculation, senescence and apoptosis of endothelial cells (ECs). A recent study demonstrated that soluble Klotho (sKl) protein interacts with the vascular endothelial growth factor receptor 2 (VEGFR-2) and with transient receptor potential canonical-1 (TRPC-1) by forming a complex on the surface of endothelial cells. This heterotrimeric complex is internalised in response to vascular endothelial growth factor (VEGF) stimulation, thus regulating VEGFR-2/TRPC-1–mediated Ca 2+ influx, to maintain endothelial biological homeostasis. The aim of this study was to evaluate, if soluble Klotho might act as protective humoral factor on SSc Microvascular Endothelial Cells (MVECs) by inhibiting cellular senescence and inducing angiogenesis. Materials and methods: Wound healing capacity was performed in healthy and SSc-MVECs under standard conditions and after sKl stimulation. Angiogenesis was evaluated by in vitro capillary morphogenesis on Matrigel in healthy and SSc-MVECs at basal condition, upon challenge with sKl, SSc and healthy sera, and sKl in combination with SSc and healthy sera. Western blot was performed in order to evaluate TRPC-1 and VEGFR-2 expression level in SSc and healthy MVECs at basal condition, after stimulation with sKl, SSc sera (n = 5), healthy sera (n = 5), and with sKl in combination with SSc and healthy sera before and after wound injury. Results: Wound healing capacity significantly increased in healthy and SSc-MVECs after sKl challenge in respect to basal condition. Angiogenesis was significantly higher in SSc-MVECs upon challenge with sKl compared to both basal SSc and healthy MVEC. Moreover, angiogenesis was significantly increased in healthy MVECs challenged with SSc sera in combination with sKl respect to MVECs with SSc sera alone. TRPC-1 and VEGFR-2 expression level significantly increased under injury in both healthy and SSc-MVECs cultured with sKl respect to basal condition. Conclusions: Our findings suggest that, under vascular injury conditions, sKl increases the wound healing ability and induces blood vessels formation in SSc-MVECs.